2023
DOI: 10.7717/peerj.14879
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of urine Raman spectra differences from patients with diabetes mellitus and renal pathologies

Abstract: Background Chronic kidney disease (CKD) poses a major public health burden. Diabetes mellitus (DM) is one of the major causes of CKD. In patients with DM, it can be difficult to differentiate diabetic kidney disease (DKD) from other causes of glomerular damage; it should not be assumed that all DM patients with decreased eGFR and/or proteinuria have DKD. Renal biopsy is the standard for definitive diagnosis, but other less invasive methods may provide clinical benefit. As previously reported, Raman spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Where SG preserves the entire Raman spectrum, ISREA can amplify regions of spectra containing disease-related information, while minimizing conserved regions. This has served to improve prediction accuracy for spectra of unknown samples in previous studies ( 32 , 33 , 36 ). Results obtained when using ISREA are presented here, and results obtained when using SG are given in the Supplementary material .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where SG preserves the entire Raman spectrum, ISREA can amplify regions of spectra containing disease-related information, while minimizing conserved regions. This has served to improve prediction accuracy for spectra of unknown samples in previous studies ( 32 , 33 , 36 ). Results obtained when using ISREA are presented here, and results obtained when using SG are given in the Supplementary material .…”
Section: Resultsmentioning
confidence: 99%
“…The locations of the nodes were adjusted to improve baseline fit and predictive capabilities. We have applied similar methods in several of our previous studies with human urine (32)(33)(34)36).…”
Section: Chemometric and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, very recently, it has been demonstrated that the evaluation of urine samples by Raman spectroscopy followed by chemometric analysis may be able to differentiate between DKD and NDKD with high specificity and sensitivity[ 82 ]. Similar results were also found in blood samples, in which the combination of traditional molecular biology and transcriptomic approaches has led to the identification of potential DKD biomarkers[ 83 , 84 ].…”
Section: What Elements May Guide Differential Diagnosis Between Dkd A...mentioning
confidence: 99%
“…This sensitive vibrational spectroscopy excites molecular bonds within a sample, providing a unique biomolecular spectral fingerprint of target biomarkers in a rapid analytical response [21,22]. These spectroscopic barcodes have been shown to identify the various diseases from which the biofluid has been collected, such as blood [23,24], CSF [25,26], urine [27,28], saliva [24,29], and tears [30,31]. In contrast to the in vitro bioassays, the availability of inexpensive, portable Raman devices makes this technique particularly attractive for point-of-care testing, analysis, and screening of biofluids.…”
Section: Introductionmentioning
confidence: 99%